(untitled) (Research, Society and Development, 2023)
Introduction: Normal childbirth is a birth process in which it has several advantages for both mother and baby. However, the associated pain often discourages pregnant women from opting for this mode of delivery. In addition, the fear of complications and the individual preferences of mothers contribute to the increase in elective cesarean section rates. However, in order to promote natural childbirth, reduce anxiety and, especially, pain, non-pharmacological methods have gained increasing acceptance, they offer comprehensive care, aiming to humanize the process and allow a delivery with as few interventions as possible. Objective: To analyze the efficacy of non-pharmacological methods in reducing pain during normal childbirth. Methods: This research is an integrative literature review that focuses on the evaluation of articles, theses and studies already published in scientific journals in the last 10 years, with the purpose of examining the efficacy of non-pharmacological methods for pain relief during vaginal delivery. Results: A total of 10 articles were selected, in which the majority (70%) adopted the design of randomized clinical trials, and to measure pain intensity, the Visual Analogue Scale was widely used. Among the nonpharmacological methods, acupuncture and its variations stand out among the most frequent. Conclusion: It is concluded that all the non-pharmacological methods analyzed demonstrated important efficacy in reducing pain during labor, however, it is not possible to classify which one is the best, since there was no significant difference between them.